Ecological Risk Assessment and Influencing Factors of Heavy-Metal Leaching From Coal-Based Solid Waste Fly Ash - Zhang, Zhiguo; Cai, Weiqing; Hu, Youbiao; Yang, Ke; Zheng, Yonghong; Fang, Chao; Ma, Chengnan; Tan, Yuning (Frontiers in Chemistry, 2022)
In order to promote and broaden the utilization of fly ash as a resource, the fly ash from a 2660 MW coal-fired power plant in Huainan (China) was investigated. The physical and chemical properties of fly ash were characterized using scanning electron microscopy, energy spectrum analysis and XRD. The content and different forms of the heavy metals Cd, Cr, Cu, Co and Ni, were determined by acid digestion, oscillation leaching and Tessier five-step extraction, respectively. The effect of pH, temperature and particle size on the leached amount of heavy metals was studied. Finally, the ecological risk index was calculated for each heavy metal via the risk assessment coding method (RAC) and Hakanson ecological risk assessment method, allowing the ecological risk of fly ash to be determined under different environmental conditions. Results showed that the average concentrations of Cd, Cr, Co and Niwere all below the risk screening values reported for environmental pollutants (pH > 7.5). Under varying pH, temperature and particle size conditions, the leached amount (oscillation leaching) was less than the soil risk screening value for agricultural land in China. An RAC-Cd value of >50% indicates a high ecological risk, while the RAC of Co and Ni were between 10% and 30%, indicating a medium ecological risk and the RAC of Cr and Cu were <10%, indicating a low ecological risk. With increasing pH conditions the potential ecological risk index (RI) decreased, with a maximum RI of 59.62 observed at pH 2.8. With increasing temperature, the potential ecological RI increased initially to a maximum of 27.69 at 25°C and then decreased thereafter. With increasing particle size the ecological RI decreased, with the highest RI of 4.06 occurring at <0.075 mm. The Hakanson ecological RI value was less than 150, indicating a slight ecological risk. Therefore, fly ash can be considered as a soil additive and conditioner, that is suitable for use in the improvement of reclamation soil in coal mining subsidence areas.